Effect of different extraction methods on yield and physico-chemical properties of garden cress (Lepidium sativam L.) oil - GB Yenge,; HG More,; RN Kenghe,; VL Kanawade,; CA Nimbalkar,; AP Patil, (Journal of Oilseed Brassica, 2026)
Effect of different extraction methods on yield and physico-chemical properties of garden cress oil wasstudied. Oil from the dried garden cress seeds were extracted by screw press, solvent extraction (withoutheating) and soxhlet extraction method. Physical properties studied were specific gravity, viscosity and colour,whereas, chemical properties analyzed were peroxide value, acid value and iodine value. Soxhlet extractionwas found to give highest yield of oil. Non-significant difference was observed for specific gravity of oilextracted by all methods. Viscosity of the oil extracted with screw press was highest (53.7 mPa.s) thansolvent extracted oil and soxhlet extracted oil (39.9 and 42.7 mPa.s, respectively). Oil extracted by soxhletmethod was darker in colour than the solvent extracted. Peroxide value (2.53 meq.kg-1) and acid value (0.74mg KOH.g-1) were higher for oil extracted with the soxhlet extraction method followed by solvent and screwpress extraction method (1.27, 0.69 meq.kg-1 and 0.83, 0.61 mg KOH.g-1, respectively) whereas, iodine valuewas highest (134.2 g I2.100g-1) for solvent extraction method followed by soxhlet extraction and screw pressmethod (131.7, 97.3 g I2.100g-1, respectively). Fatty acid profile and tocopherols content analysis of the oilextracted by soxhlet method showed that, garden cress seed oil contains 34.46 % of alfa linolenic acid and971.6 ppm total tocopherols. Oil stored in polyvinyl terephthalate bottle for 90 days showed significant increasein peroxide (25.8meq.kg-1).